THE ROLE OF SIMULATION TRAINING AND DIGITALIZATION IN THE DEVELOPMENT AND IMPROVEMENT OF EDUCATION IN MEDICAL PROFESSIONAL INSTITUTIONS (Web of Medicine: Journal of Medicine, Practice and Nursing, 2025)
In the context of the digital transformation of the healthcare system, the demand for high-quality training of mid-level medical specialists is increasing. Modern approaches to education require the introduction of innovative technologies such as simulation-based learning and the digitalization of the educational environment. This article examines the key aspects of implementing these technologies in the educational process of medical professional institutions, presents data on their effectiveness, analyzes their advantages and limitations, and substantiates the need for a systematic approach to the digital modernization of secondary professional medical education.